Effect of Pulse Therapy with Glucocorticoids and Cyclophosphamide in Patients with Paraquat Poisoning. Issue 4 (July 2015) - Ghorbani, A; Masoumi, K; Forouzan, A; Rahmani, Ah; Rahim, F; Taeybi, B Taherinezhad; Feli, M
Introduction: Paraquat (PQ) is a widely used herbicide with a high mortality rate when ingested. The aim of the present study was to assess the effectiveness of repeated cyclosphosphamide (CP) and methylprednisolone (MP) combination in the treatment of PQ poisoning. Design: Randomised, double-blinded, placebo-controlled trial. Methods: Eligible participants were 47 patients with moderate to severe PQ poisoning within 24 hours of hospitalisation. Patients were allocated in a random fashion, 24 as the intervention and 23 as the control group. All patients received two cycles of eight hours of haemoperfusion with charcoal, and underwent emergency haemodialysis. After the dialysis, the intervention group received 15 mg/kg CP for two days and 1g MP for three days. The control group received routine supportive care. Outcome parameters, including mortality, incidence of hypoxia, hepatitis and renal failure were compared between the two groups. Results: There were no significant differences between the two groups with regard to age, sex, baseline liver function test, creatinine, time from poisoning to dialysis, and time from poisoning to the hospitalisation. Although the incidence of hepatitis and acute renal failure did not differ significantly between the two groups, the incidence of hypoxia and mortality rate was lower in the intervention group. The number need-to-treat to reduce one mortality was 2.8. Conclusion: The results suggest that CP and MP repeated treatment can reduce the mortality rate in moderate to severe PQ intoxication.